Time Frame and Syllabus Completion of Senior Secondary Mathematics in Omoku, Nigeria - Allison, Dimkpa Solomon; Olugbade, Ojedapo David (Richtmann Publishing, 2011)
The study considered time allocated against syllabus completion before external examinations. The focal points weremathematics as a subject and an analysis of the 2009/2010 Academic Session. The analysis revealed that out of 364days in asession, only 146 days, represented 40% of the entire session did schools engaged in various school activities. The remaining218 days, representing 60% of the session was observed as different holidays, making time frame to be inadequate andinsufficient for mathematics syllabus completion. Three theories: Total Quality Management (TQM), Quality Assurance (QA)and Theory Z were posited as frameworks. Recommendations such as more periods should be allocated for completion ofmathematics syllabus before exposing students to external examinations and others were postulated.